Micro Dynamics of Turkey's Export Boom in the 2000s - Cebeci, Tolga; Fernandes, Ana M. (World Bank, Washington, DC, 2013)
This paper examines the microeconomics behind the dramatic export boom experienced by Turkey during the 2000s. Using disaggregated customs data covering the universe of export transactions for Turkey during the period 2002-2011, it characterizes firm-level dynamics in the export sector and decomposes export growth at the aggregate, sector, and destination market levels to identify the role of firm turnover, destination turnover, and product turnover. The paper shows that in the short-run, aggregate export growth is dominated by growth in continuous exporters, and for these, growth is dominated by exports to their continued destinations and of their continued products. However, the observed high degree of churning across firms, destinations, and products accounts in the long run for a substantial part of Turkey's export growth. The patterns of micro-dynamics of export growth are verified across sectors and across groups of destination markets with some exceptions regarding exports to new emerging markets where net entry by Turkish-based exporters plays a more critical role for long-run growth.